Immunisation Status of Children born with Orofacial Clefts Who Visited the Komfo Anokye Teaching Hospital (KATH) multidisciplinary Cleft Clinic. - Acheampong, Alexander Oti; Obiri – Yeboah, Solomon; Owusu, Alex Ansah; Amuasi, Ama; Plange – Rhule, Gyikua; Donkor, Peter (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
The Ghana Expanded Programme on Immunisation recommends thatchildren receive Bacillus Calmette-Guerin (BCG) and Oral Polio Vaccine (OPV) atbirth; three doses of Penta vaccine and OPV at 6, 10 and 14 weeks of age; andmeasles vaccine at 9 months of age.